2020
DOI: 10.3389/fonc.2020.00042
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Survival and Risk Factors of Differentiated Thyroid Cancer in the Geriatric Population

Abstract: Purpose: The incidence rate of differentiated thyroid cancer (DTC), the most common type of thyroid cancer, has increased in the past two decades. The present study analyzed the clinical and pathological characteristics of DTC, and discussed the risk factors for survival in elderly age-risk DTC patients.Methods: Elderly patients who were diagnosed with DTC, and subsequently underwent surgery for DTC, were identified from the SEER database . Based on histology, these patients were divided into C-PTC, FV-PTC, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 41 publications
4
16
0
1
Order By: Relevance
“…In our study, we found that an age of 55 years is a clearly useful cut-off threshold for stratifying PTC patients, with patients younger and older than this age having better and poorer prognoses, respectively, consistent with a recent study (14). Those authors used Cox proportional hazards analysis to assess the association between speci c risk factors and the prognosis of WDTC and showed, consistent with our ndings, that an age of 55 years is an effective cut-off threshold for risk strati cation in PTC patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, we found that an age of 55 years is a clearly useful cut-off threshold for stratifying PTC patients, with patients younger and older than this age having better and poorer prognoses, respectively, consistent with a recent study (14). Those authors used Cox proportional hazards analysis to assess the association between speci c risk factors and the prognosis of WDTC and showed, consistent with our ndings, that an age of 55 years is an effective cut-off threshold for risk strati cation in PTC patients.…”
Section: Discussionsupporting
confidence: 92%
“…The current 8 th Edition AJCC TNM classi cation system uses an age of 55 years as a cut-off point for risk strati cation in tumor staging (13). By contrast, the previous traditional TNM staging system used an age of 45 years (13) as a cut-off for staging, and the change to 55 years prompted a debate regarding how clinically well-founded this age cutoff point is for PTC risk strati cation, with some authors questioning the utility of using either threshold for risk strati cation (14) and others proposing that the age threshold for staging PTC should be further increased (8). For example, a previous study showed that in PTC, overall survival decreases incrementally with age and that the optimal age threshold for PTC patients is 58.5 years (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current 8 th Edition AJCC TNM classi cation system uses an age of 55 years as a cut off point for risk strati cation in tumor staging (13). By contrast, the previous traditional TNM staging system used an age of 45 years (13) as a cut off for staging, and the change to 55 years prompted a debate regarding how clinically wellfounded this age cut off point is for PTC risk strati cation, with some authors questioning the utility of using either threshold for risk strati cation (14) and others proposing that the age threshold for staging PTC should be further increased (8). For example, a previous study showed that in PTC, overall survival decreases incrementally with age and that the optimal age threshold for PTC patients is 58.5 years (8).…”
Section: Introductionmentioning
confidence: 99%
“…The same researchers (8) also proposed that in terms of the age threshold for risk strati cation, PTC should not be evaluated using the same criteria as those used for FTC, and these conditions should instead be viewed as different forms of WDTC. Other authors have proposed that among older patients, there is no suitable age cut off for decreasing surveillance (14). Hence, while many authors agree that age is one of the most important factors for risk strati cation, there is disagreement regarding what the age cut off should be or whether such a cut off should be applied at all (15).…”
Section: Introductionmentioning
confidence: 99%